A method of integrating CALPHAD data into phase-field models using an approximated minimiser applied to intermetallic layer growth in the Al-Mg system. (December 2017) - Welland, M.J.; Piro, M.H.A.; Hibbins, S.; Wang, N.
Abstract: This article describes an approach to combine single phase thermodynamic potentials into a multiphase composite potential suitable for integration in a multicomponent phase-field model. The composite potential avoids implicit interfacial energy contributions by starting from a grand potential formulation. The method is made explicit by expanding the minimiser resulting from the Legendre transform between grand and Helmholtz potentials about a known equilibrium state. The resulting composite function is explicit, reproduces the equilibrium states exactly, and is smooth such that it can be differentiated to provide the driving forces for mass transport and phase change in a thermodynamically self-consistent manner. The model is demonstrated by simulating a sequence of phase transformations for intermetallic growth in Al-Mg interdiffusion for advanced nuclear research reactor fuel.